Perilaku Petani dalam Penerapan Inovasi Pertanian Berkelanjutan pada Usahatani Hidroponik di Kota Kendari - Rania Alini Az Zahra; Sukmawati Abdullah; salahuddin salahuddin (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
This study aims: (1) to find out how the behavior of farmers in hydroponic farming in Kendari City; (2) To find out how the application of sustainable agricultural innovation in hydroponic farming in Kendari City; (3) To find out how the relationship between farmer behavior and the application of sustainable agricultural innovations in hydroponic farming in Kendari City. The population in this study using the census technique, namely the entire population of 25 people identified at the Kendari City Agriculture Office. This study was analyzed descriptively with a quantitative approach using the interval formula and quantitative inferential with the Spearman rank correlation formula. The results showed that; The behavior of hydroponic farming farmers in Kendari City it's classified as moderate. This show that farmers have sufficient knowledge, attitudes and skills in hydroponic farming in Kendari City that they still need to be improved, especially on the aspect of nutrient solution provision and planting indicators.